Pengembangan Media Pembelajaran Infografis Interaktif Berbasis Aplikasi Canva pada Mata Pelajaran SKI (Sejarah Kebudayaan Islam) di MTsN 9 Agam - Dina Apriyani; Puti Andam Dewi (YASIN, 2026)
The use of digital-based learning media in the teaching of Islamic Cultural History (SKI) has received attention in various studies, but studies that specifically develop and examine the effectiveness of Canva-based interactive infographic media on the topic of Muslim scholar figures remain limited. This study aims to develop and evaluate the validity, practicality, and effectiveness of Canva-based interactive infographic learning media in improving the quality of SKI learning. This study used a mixed methods approach with an ADDIE model Research and Development design. The study involved one class, namely VIII F at MTsN 9 Agam, as the trial subject, as well as nine expert validators consisting of media, material, and language experts selected through purposive sampling. Data were collected using validation questionnaires, practicality questionnaires, effectiveness questionnaires, as well as interviews and observations, and were then analyzed descriptively using qualitative and quantitative approaches. The results showed that the developed media had a validity level of 91.42% in the very valid category, a practicality level of 94.3% in the very practical category, and an effectiveness level of 93% in the very effective category. These findings indicate that interactive infographic media are able to improve students’ understanding of the material, motivation, and learning independence. The conclusion of the study emphasizes the importance of integrating visual-interactive media in learning as well as the need to optimize teachers’ use of technology to improve learning quality. The implications of this study include a theoretical contribution to the development of digital learning media and a practical contribution for teachers in improving learning quality, while also opening opportunities for the development of similar media in broader contexts and materials.